Sustainable and Environment-Friendly Management of Shrimp Processing Waste through High-Quality Chitosan Production - Zulkarnain, Zulkarnain; Mukti, Wiji Aziiz Hari; Kurniawan, Kurniawan (Leuser Journal of Environmental Studies, 2024)
The shrimp processing industry generates substantial waste, including shells, heads, and tails, which, if not properly managed, can contribute to significant environmental issues, such as pollution and disease transmission. This study explores the conversion of shrimp waste into chitosan, a valuable biopolymer with applications across multiple industries, by utilizing its chitin, protein, and mineral content. The extraction process involved demineralization with 1M HCl, deproteinization with 3.5% NaOH, and deacetylation with 60% NaOH. The resulting chitosan exhibited high quality, characterized by a crystal structure, white color, odorless powder form, 73.7% degree of deacetylation (DD), 64% yield, solubility in acetic acid, and water content of 1.5%. This research highlights an environmentally responsible approach to shrimp waste management, providing a method for repurposing waste into a high-value material that meets industry standards, supporting environmental sustainability and circular economy practices.